Understanding Differences in Wayfinding Strategies - Hegarty, Mary; He, Chuanxiuyue; Boone, Alexander P.; Yu, Shuying; Jacobs, Emily G.; Chrastil, Elizabeth R. (Topics in cognitive science, 2023)
Navigating to goal locations in a known environment (wayfinding) can be accomplished by different strategies, notably by taking habitual, well‐learned routes (response strategy) or by inferring novel paths, such as shortcuts, from spatial knowledge of the environment's layout (place strategy). Human and animal neuroscience studies reveal that these strategies reflect different brain systems, with response strategies relying more on activation of the striatum and place strategies associated with activation of the hippocampus. In addition to individual differences in strategy, recent behavioral studies show sex differences such that men use place strategies more than women, and age differences such that older adults use more response strategies than younger adults. This paper takes a comprehensive multilevel approach to understanding these differences, characterizing wayfinding as a complex information processing task. This analysis reveals factors that affect navigation strategy, including availability of the relevant type of environmental knowledge, momentary access to this knowledge, trade‐offs between physical and mental effort in different navigation contexts, and risk taking. We consider how strategies are influenced by the computational demands of a navigation task and by factors that affect the neural circuits underlying navigation. We also discuss limitations of laboratory studies to date and outline priorities for future research, including relating wayfinding strategies to independent measures of spatial knowledge, and studying wayfinding strategies in naturalistic environments. This paper examines factors that wayfinding strategies such as following well‐learned routes versus taking novel shortcuts. We consider how strategies are influenced by availability of different types of environmental knowledge, by the computational and physical demands of different wayfinding tasks, and by hormonal states that affect the neural circuits underlying navigation.